STUDENTS' PERCEPTIONS ON ONLINE LEARNING AT TADRIS BAHASA INGGRIS DURING THE COVID-19 PANDEMIC - Pratama, Aryawira (E-Link Journal, 2023)
One of the hot issues in learning English in pandemic covid-19 is the online learning method. This research aimed to know the students' perception of online learning English during the covid pandemic at Tadris Bahasa Inggris in Jambi. The design of this research is a survey that used of quantitative method. The data were collected using a questionnaire consisting of 20 questions divided into three dimensions. There were 50 participants which able to give their responses to the questionnaire. The questionnaire was distributed through google form to know the perception of students in the fourth semester who learn English using the online method. This research showed that online learning English during the covid pandemic got a positive perception. It could be seen from the result of the table distribution, which showed a 60% percentage for the dimension of teaching material, 54% for the dimension of atmosphere or learning environment, and 66% for the dimension of students' interaction. Keywords: Online learning, Covid pandemic, perception